If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(15) + -5y = 15 Multiply -3 * 15 -45 + -5y = 15 Solving -45 + -5y = 15 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + -5y = 15 + 45 Combine like terms: -45 + 45 = 0 0 + -5y = 15 + 45 -5y = 15 + 45 Combine like terms: 15 + 45 = 60 -5y = 60 Divide each side by '-5'. y = -12 Simplifying y = -12
| 1/2(4x+8)=1.3-(x+2) | | -3.14(16)+502.4=h | | 1/4x+3=2x+3/4 | | 2x+12=-3x-8+7x | | -19.2=-3.6x+2.4 | | x*2-2=8 | | 5+8m=11 | | a/2+2/4=4a/5+5/3 | | N/0.3=66.666666666666 | | -4(-e+3f)-3(e+(-5f))=0 | | W-6.34=4.63 | | 17a+4a-20a+a=14 | | 5c-6d=3 | | 98+3x-17=180 | | 28=2x+6(4x-17) | | .625=.25-.5p | | x*2+9=17 | | -5m+2(m+2)=m+4(2m-5) | | 3(n-1l)=5n+3-2n | | 3x+3=-1+2x+11 | | 1c-4+5*c-4=70 | | 4z-10+z=90 | | 5y-3=117 | | 3t^2+6t+3=0 | | 1/.38= | | 8x+4(4x-3)=4(6x+4)+4 | | 3(x+2)-5=7x-(4x-1) | | -24=-y/6 | | 7.1a=1.5 | | 4w+2W-3=33 | | 0.7(5x+10)=1.2-(x+2) | | 7-8x-3x=-14-8x |